Thrombosis and lymphocyte subsets of COVID-19 omicron BA.2 variant patients with cancer - Yin, Jiaxin; Cong, Xiaofeng; Wang, Nanya; Song, Wei; Guan, Yanjie; Zhang, Yiqun; Li, Zhi; Liu, Ziling (Frontiers in Oncology, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) caused an ongoing global pandemic of COVID-19. It has been found that COVID-19 has an influence on the changes of blood coagulation parameters and the high incidence of thrombosis. Changchun experienced the epidemic of the Omicron BA.2 variant SARS-CoV-2 in March 2022 in China. Once infected, BA.2 spreads rapidly and most of them are asymptomatic. The purpose of this study is to research venous thrombosis and laboratory changes (including PLT, PT, APTT, DD, FDP, CRP, WBC, IL-6 and lymphocyte subsets) among 92 cancer patients with COVID-19 and 73 COVID-19 patients with non-cancer by Mann-Whitney U and Chi-square test. It was found that the levels of D-dimer, FDP, CRP and IL-6 in cancer patients were significantly higher than those in the COVID-19 cohort. There were 9 (9.8%) cancer patients and 2 (2.7%) non-cancer patients found VTE, with no significant difference. The results showed that WBC, lymphocytes and B cells in cancer patients were significantly lower than those in the other group. Prophylactic anticoagulation was recommended for cancer patients with high risk factors, while paying attention to the occurrence of bleeding events. The detection of leukocyte classification, D-dimer, prothrombin time and fibrinogen at different time points are helpful for the diagnosis and anticoagulation of COVID-19 patients with cancer.